Nano-mole scale sequential signal assignment by 1H-detected protein solid-state NMR. Issue 81 (28th August 2015) - Wang, Songlin; Parthasarathy, Sudhakar; Xiao, Yiling; Nishiyama, Yusuke; Long, Fei; Matsuda, Isamu; Endo, Yuki; Nemoto, Takahiro; Yamauchi, Kazuo; Asakura, Tetsuo; Takeda, Mitsuhiro; Terauchi, Tsutomu; et al.
Abstract : We present a 3D 1 H-detected solid-state NMR (SSNMR) approach for main-chain signal assignments of 10–100 nmol of fully protonated proteins. Abstract : We present a 3D 1 H-detected solid-state NMR (SSNMR) approach for main-chain signal assignments of 10–100 nmol of fully protonated proteins using ultra-fast magic-angle spinning (MAS) at ∼80 kHz by a novel spectral-editing method, which permits drastic spectral simplification. The approach offers ∼110 fold time saving over a traditional 3D 13 C-detected SSNMR approach.